bric à brac controls sex pheromone choice by male European corn borer moths - Unbehend, Melanie; Kozak, Genevieve M.; Koutroumpa, Fotini; Coates, Brad S.; Dekker, Teun; Groot, Astrid T.; Heckel, David G.; Dopman, Erik B. (Nature communications, 2021)
The sex pheromone system of ~160,000 moth species acts as a powerful form of assortative mating whereby females attract conspecific males with a species-specific blend of volatile compounds. Understanding how female pheromone production and male preference coevolve to produce this diversity requires knowledge of the genes underlying change in both traits. In the European corn borer moth, pheromone blend variation is controlled by two alleles of an autosomal fatty-acyl reductase gene expressed in the female pheromone gland ( pgFAR ). Here we show that asymmetric male preference is controlled by cis -acting variation in a sex-linked transcription factor expressed in the developing male antenna, bric à brac ( bab ). A genome-wide association study of preference using pheromone-trapped males implicates variation in the 293 kb bab intron 1, rather than the coding sequence. Linkage disequilibrium between bab intron 1 and pgFAR further validates bab as the preference locus, and demonstrates that the two genes interact to contribute to assortative mating. Thus, lack of physical linkage is not a constraint for coevolutionary divergence of female pheromone production and male behavioral response genes, in contrast to what is often predicted by evolutionary theory. Many organisms, including moths, use pheromones to attract mates. A study using multiple genomic tools and gene editing identifies a new, neuronal gene underlying mate preference and shows that signal and response loci are in linkage disequilibrium despite being physically unlinked.